Penerapan Green Economy Dalam Upaya Pencegahan Kerusakan Lingkungan Pada PT MHE Demag Indonesia - Zufi Yustika Magitasiwi; Zahra Febriana Taufiq; Soputan, Sylvia Setyani; Maria Yovita R. Pandin (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research was conducted at PT MHE Demag Indonesia in the city of Surabaya to determine the application of green economy in efforts to prevent environmental damage at PT MHE Demag Indonesia. This research uses qualitative methods obtained by taking primary data and secondary data through observation, interviews and documentation. The results of this research show that PT MHE Demag Indonesia has implemented the provisions of the Republic of Indonesia Government Regulation No. 22 of 2021 and carried out its environmental obligations through social activities around the company environment.